Discriminating between neuropathic pain and sensory hypersensitivity using the Chronic Pain Questions (CPQ). Issue 1 (2nd January 2017) - Coyne, Karin S.; Currie, Brooke M.; Donevan, Sean; Cappelleri, Joseph C.; Hegeman-Dingle, Rozelle; Abraham, Lucy; Thompson, Christine; Sadosky, Alesia; Brodsky, Marina
ABSTRACT: Objective : The Chronic Pain Questions (CPQ) were developed for clinical use with the aim of supporting primary care physicians in the screening, assessment and monitoring of patients with chronic pain. the purpose of this study was to examine the ability of the cpq CPQ to discriminate between patients with neuropathic pain (nep) versus those with sensory hypersensitivity (sh). Methods : Adult men and women with a diagnosis of a NeP or SH condition were recruited from 5 clinical sites across the United States. Participants completed a series of self-administered questionnaires, including the CPQ. Continuous variables were compared between groups with independent t-tests; categorical variables were compared with chi-square analyses. A series of exploratory logistic regressions were performed to discern optimal screening criteria for SH using CPQ responses. Results : 98 participants, 68 with physician-confirmed diagnoses of SH and 30 with NeP, participated. 81.6% were female, 73.5% Caucasian, and mean (± SD) age was 58.4 ± 12.6 years. SH participants included significantly more females compared to the NeP group (94.1% vs. 53.3%). Differences in CPQ responses between groups were statistically significant for six of the 14 CPQ items with SH participants having significantly lower scores on specific pain quality questions and significantly higher scores on trouble thinking/remembering (5.3 ± 3.5 vs. 3.0 ± 2.8) and sensitivity to lights/noises/smells (4.8 ± 3.5 vs. 2.7 ± 3.0). No significant differences were found between groups for chronic pain intensity, pain made worse with touch, pain limited to joints, or pain interference with usual activity, sleep or mood. Logistic regression analyses revealed strong c indices (≥0.89) for all models. Consistent findings demonstrated that younger age, female gender, and scores ≥6 for the CPQ question on sensitivity to lights/noises/smells were all predictive of SH. Conclusions : The CPQ can help differentiate between patients with NeP and SH. More research is warranted.